Kesiapan Tenaga Administrasi Sekolah Menerima Perubahan pada SMP Negeri Se Kota Padang - Beuty, Sarah; Rusdinal, Rusdinal; Anisah, Anisah; Santoso, Yulianto (Lembaga Yasin AlSys, 2024)
This research is based on the results of an interview with the head of school administration staff at SMP Negeri Kota Padang. This study aims to obtain information about the readiness of school administration personnel to accept change in terms of three aspects, namely, mental readiness, knowledge readiness and participation in change. This research is a descriptive quantitative research. The population in this study is all school staff in the city of Padang. The number of samples in this study was 83 people. The instrument used in the questionnaire is a semantic differential semantic scale. The steps taken in analyzing data are, verifying data, tabulating data, calculating the average value (mean) then looking for the percentage of score achievement and describing the data processed based on specified criteria. This study shows the results of the readiness of administrative personnel to accept changes in public junior high schools in Padang City as seen from the indicators (1) Mental readiness with the ready category and 80.10% achievement rate, (2) Knowledge readiness with the ready category and 81.02% achievement rate, (3) Participation in changes with the ready category and 80.19% achievement rate. It can be concluded that the readiness of school administration personnel in accepting changes in public junior high schools in Padang City can be categorized as ready to accept changes with an achievement level (8, 0.44%).